Traditional Chinese Medicine as a Promising Strategy for the Treatment of Alzheimer’s Disease Complicated With Osteoporosis - Xu, Weifan; Jiang, Yiping; Wang, Nani; Bai, Huanhuan; Xu, Shengyan; Xia, Tianshuang; Xin, Hailiang (Frontiers in Pharmacology, 2022)
Alzheimer's disease (AD) and osteoporosis (OP) are both progressive degenerative diseases caused by multiple factors, placing a huge burden on the world. Much evidence indicates that OP is a common complication in AD patients. In addition, there is also evidence to show that patients with OP have a higher risk of AD than those without OP. This suggests that the association between the two diseases may be due to a pathophysiological link, rather than one disease causing the other. Several in vitro and in vivo studies have also proved their common pathogenesis. Based on the theory of traditional Chinese Medicine, some classic and specific natural Chinese medicines are widely used to effectively treat AD and OP. Current evidence also shows that these treatments can ameliorate both brain damage and bone metabolism disorder, and further alleviate AD complicated with OP. These valuable therapies might provide effective and safe alternatives to major pharmacological strategies.